The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.jasms.2003.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy in quadrupole mass spectrometry

Abstract: Application of an analytical solution of the Mathieu equation in conjunction with algebraic presentation of the Mathieu functions for description of the ion energy in a radiofrequency quadrupole field is discussed in this work. The analytical approach is used to express the ion energy averaged over the initial ion velocity distribution function, field phase and ion residence time. Comparisons with the approximate solutions for potential ion energy are presented with demonstration of their limits. Application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…It should be noted that the ions entering the collision cell already possess a significant amount of internal energy, resulting, e.g., from collisions with gas-phase solvent and desolvation gas in the ion source, 1,15 thermal energy, 15 and radial acceleration in the RF-field. 19 There are additional molecular features of deprotonated 12,13-(OH) 2 -18:0 that enhance the weakening of the C a -H and C a -C bonds adjacent to a hydroxyl group and thus may facilitate C a -H cleavage. Anderson et al found, by both theoretical computations and laboratory experiments, that the vibrational frequency (n C-D ) of a C a -D bond of an alcohol decreased when the hydroxyl group participated in H-bonding.…”
mentioning
confidence: 99%
“…It should be noted that the ions entering the collision cell already possess a significant amount of internal energy, resulting, e.g., from collisions with gas-phase solvent and desolvation gas in the ion source, 1,15 thermal energy, 15 and radial acceleration in the RF-field. 19 There are additional molecular features of deprotonated 12,13-(OH) 2 -18:0 that enhance the weakening of the C a -H and C a -C bonds adjacent to a hydroxyl group and thus may facilitate C a -H cleavage. Anderson et al found, by both theoretical computations and laboratory experiments, that the vibrational frequency (n C-D ) of a C a -D bond of an alcohol decreased when the hydroxyl group participated in H-bonding.…”
mentioning
confidence: 99%
“…The reaction mechanism for the 2Me-thiophene was not further explored since we were interested only in explain the low yield of reaction 2 in this case. The energy necessary to overcome the barrier to the insertion product can derive from a contribution of the radio frequency field to the ion energy [30][31][32].…”
Section: Computational Studymentioning
confidence: 99%
“…-on motion stability and resonance phenomena in quadrupole traps and filters used in mass spectrometers [10,[12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%